Modelling and Controller Design for a Flexible Structure System against Disturbance Effects. Issue 4 (December 2015) - Tinkir, Mustafa; Kalyoncu, Mete; ŞLahin, Yusuf
The effects of natural hazards such as earthquakes are serious threat to structures and most researchers have studied structural control systems. Vibration and displacement control of structures under seismic excitation are important problems for which a solution is to use structural control against the disturbances. This paper presents modelling and controller design for flexible structure systems against unexpected disturbance effects such as seismic excitation. The proposed system consists of two flexible floors with active mass damper. The system is set up on a shake-table and disturbances are created by the shake-table. Active mass damper consists of a moving mass actuated by a servomotor, which moves linearly and is mounted on the second floor to suppress structural vibrations and displacements. In simulation works, different types of modeling technique are used to obtain dynamic behaviour of the proposed system and control of the simulated system is carried out using SolidWorks and MATLAB/SimMechanics. Moreover linear quadratic regulator and proportional-integral-derivative controllers are designed to control the moving mass in active mode while the system is under excitation. For this purpose a full-order observer is formed and implemented as control strategy. Furthermore acceleration and displacement responses of the floors and displacement of proportional velocity controlled cart are investigated in passive mode. A set of results verifying the modelling technique, controller performance and effectiveness, displacements of cart, displacements and accelerations of the floors are presented and compared separately for passive and active modes in the form of graphics and tables.